2002
DOI: 10.1046/j.1439-0450.2002.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Exposure to Low‐Dose Fumonisin B1 in Pigs

Abstract: From the point of view of human exposure, fumonisins (FB1, FB2, FB1, FB4), a relatively recently (1988) discovered and identified group of mycotoxins, represent one of the five most important mycotoxin groups causing human disease. In an earlier experiment studying the effects of relatively low doses (10, 20 and 40 p.p.m.) of FB1 in weaned piglets, it was established that the 4-week feeding of 10 p.p.m. (mg/kg feed) FB1 produced mild pulmonary oedema. This suggested the importance of studies with even lower do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 10 publications
1
26
1
Order By: Relevance
“…These results are consistent with those of previous studies performed on conventional piglets fed diets containing 1 to 10 ppm FB 1 for 4 to 8 weeks [10,29,30]. These studies did not show any deleterious effects of fumonisins on either the performance or health of piglets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those of previous studies performed on conventional piglets fed diets containing 1 to 10 ppm FB 1 for 4 to 8 weeks [10,29,30]. These studies did not show any deleterious effects of fumonisins on either the performance or health of piglets.…”
Section: Discussionsupporting
confidence: 93%
“…Fumonisins have a molecular structure similar to that of sphinganine (Sa) and sphingosine (So), both of which are cell components of the carbon skeleton of sphingolipids, and which affect the Sa/So ratio. Both [9] and [10] found an increased Sa/So ratio in serum from pigs fed FB 1 at concentrations of ≥5 ppm. This increase in the ratio is considered to be a dose-dependent early marker of exposure to fumonisins [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study with purified toxin, biochemical changes were only observed at early (2 weeks) or late (8 weeks) time points (Rotter et al 1996). No significant effect of FB 1 from fungal culture material was observed on blood parameters (Zomborszky-Kovacs et al 2002).…”
Section: Discussionmentioning
confidence: 75%
“…According to Zomborszky-Kovács et al (2002), 1,000 µg kg −1 of FB1 was considered a tolerable concentration for pigs, thus the concentration of FB1 in the current study would not be the major cause for the reduction in growth performance of pigs. The overall reductions in ADG and G: F of pigs fed diet 4 compared with diet 1 were 6.4 and 2.7%, respectively.…”
Section: Discussionmentioning
confidence: 87%